DEVELOPMENT OF TEACHING MATERIALS FOR WRITING POETRY BASED ON CONTENT AND LANGUAGE INTEGRATED (CLIL) FOR X GRADE - Kristanti, Kristanti; Boeriswati, Endry; Rohman, Saifur (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to develop CLIL-based poetry writing teaching materials for grade X students. The method used is Research and Development (R&D) with the ADDIE model consisting of five stages: analysis, design, development, implementation, and evaluation. The results of the needs analysis showed that most grade X students in high school had difficulty in determining topics or themes and in choosing words when writing poetry. In addition, teachers still rely on teaching materials from textbooks. Therefore, the development of this teaching material is important and innovative to answer these problems. This CLIL (Content and Language Integrated Learning) based teaching material is expected to improve students’ writing skills while enriching their cultural understanding. Before being implemented, the teaching materials were validated by material experts, language experts, and display experts. The validation results showed an average score of 93.85%, which was categorized as very feasible to use. Furthermore, the teaching materials were implemented to grade X students in high school. The post-test and evaluation stage showed that this teaching material was valid and effective, with a significant improvement in students’ poetry writing skills, especially in determining the theme and using the elements of poetry. In addition, the results of interviews with teachers at the evaluation stage showed a positive response to the teaching materials developed. Thus, this teaching material is declared feasible to use.